The Impact of Online Media on Legal Discourse - Artur Kotowski (Studia Iuridica Lublinensia, 2023)
This article examines the methodological challenges and difficulties created by the emergence of new forms of legal discourse. These are provided by the new channels of communication, collectively found within the “mass media” and concerns online media: portals, blogs, social networking applications, etc. Since analytical theories of legal discourse were developed before the IT revolution, it is important to consider to what extent existing theories of legal discourse are adequate, given the contemporary picture of the phenomenon. The article is scientific but also contains some reflexions in the field of legal methodology due to its subject. There are formulated two research theses. The first concerns the assumption that due to the expansion of mass media, legal discourse is losing its previous hermetic character. The second assumes that the research programme of analytical jurisprudence, within which previous theories of legal discourse have been developed, requires appropriate modifications to capture the new forms in which it is conducted. The paper concludes by formulating possible directions for the development of a methodology for creating theories of legal discourse.